CURRENT APPROACHES TO TEAMWORK IN PROFESSIONAL FOREIGN LANGUAGE CLASSROOM - Рекун, Наталія (SWorldJournal, 2026)
The article analyzes such a method of group learning as teamwork of students in professional foreign language classroom. There was introduced a list of factors that led to changes in the educational environment of university students of Ukraine. The relev